2004
DOI: 10.1345/aph.1d531
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Drug-Related Problems in Different Patient Groups

Abstract: DRPs occurred in the majority of the patients in all departments. The type of DRP differed markedly between the patient groups. Knowledge of these differences is clinically valuable by enabling us to guide efforts toward prevention of DRPs. Antithrombotic agents, loop diuretics, angiotensin-converting enzyme inhibitors, penicillins, antiinflammatory drugs, and opioid analgesics commonly caused DRPs, even in departments where knowledge of these drugs is assumed to be extensive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 23 publications
(27 reference statements)
6
31
1
1
Order By: Relevance
“…Of potential risk factors for DRPs (see Methods) polypharmacy ( ‡5 drugs) occurred most commonly (47.4% of the patients), followed by the use of drugs with a narrow therapeutic index (29.1%), reduced renal function (18.9%), cardiac failure (18.1%), previous allergy or adverse events to drugs (15.2%), diabetes mellitus (11.3%) and others (15.4%). The drug groups causing most problems were antitrombotic agents, NSAIDs and opioids; details have been reported elsewhere [1,2].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of potential risk factors for DRPs (see Methods) polypharmacy ( ‡5 drugs) occurred most commonly (47.4% of the patients), followed by the use of drugs with a narrow therapeutic index (29.1%), reduced renal function (18.9%), cardiac failure (18.1%), previous allergy or adverse events to drugs (15.2%), diabetes mellitus (11.3%) and others (15.4%). The drug groups causing most problems were antitrombotic agents, NSAIDs and opioids; details have been reported elsewhere [1,2].…”
Section: Resultsmentioning
confidence: 99%
“…Drug therapy is growing more complex, thus making appropriate drug prescribing increasingly challenging. In a previous study we found one or more DRPs in about four fifth of the patients in general hospitals and also identified risk factors for DRPs [1,2]. A multidisciplinary approach, including clinical pharmacists addressing DRPs, has been shown to reduce the frequency of DRPs [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…During the last 20 years clinical pharmacist became a unique and efficient member of the healthcare team and contributed substantially to the wellbeing of patients in the different health care settings [10][11][12][13][14][15][16][17][18][19][20][30][31][32][33]. Despite this, clinical pharmacy is very slowly progressing in the developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence and nature of DRPs have been investigated previously in inpatients, outpatients and other clinical settings [10][11][12][13][14][15][16][17][18][19][20]. However, many of these studies had methodological problems related to their design, retrospective nature, definition of DRPs or to the lack of appropriate assessment of patients data.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of hospitalised patients have drug-related problems (DRPs) [1][2][3][4][5][6][7][8][9][10][11] which are events or circumstances involving drug therapy that actually or potentially can interfere with the desired health outcomes [12]. The total cost of drug-related morbidity and mortality exceeds the cost of the medications themselves [3].…”
Section: Introductionmentioning
confidence: 99%